Developing Work Practices and Sustainable Talent Management of Autonomous Agile Teams - Aluwi, Ainie Hairianie; Omar, Muhamad Khalil; Hussein, Norashikin; Mohd, Idaya Husna; Rusdi, Syezreen Dalina (Advances in Social Sciences Research Journal, 2023)
The purpose of this research is to examine the practice behind sustainable agile work practices. In the wake of Covid-19, organizations need to understand the importance of agile development processes to be able to continue doing business. This study looks at a process made popular by software engineering development in the context of post covid organization. This study takes consideration into existing social-psychology research from a human resource perspective. Namely, this study will examine group socialization and how much new members of the organization contribute to the group, particularly in sustaining organization goals.